2017
DOI: 10.1021/acs.jnatprod.7b00019
|View full text |Cite
|
Sign up to set email alerts
|

A Maldiisotopic Approach to Discover Natural Products: Cryptomaldamide, a Hybrid Tripeptide from the Marine Cyanobacterium Moorea producens

Abstract: Genome sequencing of microorganisms has revealed a greatly increased capacity for natural products biosynthesis than was previously recognized from compound isolation efforts alone. Hence, new methods are needed for the discovery and description of this hidden secondary metabolite potential. Here we show that provision of heavy nitrogen 15N-nitrate to marine cyanobacterial cultures followed by single filament MALDI analysis over a period of days was highly effective in identifying a new natural product with an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
50
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(58 citation statements)
references
References 48 publications
(103 reference statements)
6
50
0
2
Order By: Relevance
“…Moreover, the MS/MS fragmentation pattern matched the previously reported fragmentation pattern of cryptomaldamide ( Figure 4B). 16 These data provided preliminary confirmation of heterologous production of cryptomaldamide in Anabaena. (Table S2).…”
Section: Heterologous Expression Of the Cryptomaldamide Bgc In Anabaenamentioning
confidence: 57%
See 2 more Smart Citations
“…Moreover, the MS/MS fragmentation pattern matched the previously reported fragmentation pattern of cryptomaldamide ( Figure 4B). 16 These data provided preliminary confirmation of heterologous production of cryptomaldamide in Anabaena. (Table S2).…”
Section: Heterologous Expression Of the Cryptomaldamide Bgc In Anabaenamentioning
confidence: 57%
“…(Table S2). 16 Additionally, two singlets at δH 8.03 -8.09 and a singlet at δH 7.78 were indicative of the presence of a monosubstituted guanidine group. Taken together, these data confirmed that cryptomaldamide was being produced in the heterologous host Anabaena.…”
Section: Heterologous Expression Of the Cryptomaldamide Bgc In Anabaenamentioning
confidence: 99%
See 1 more Smart Citation
“…Conventionally, spectra of a natural product obtained by liquid chromatography–mass spectrometry, nuclear magnetic resonance and infrared spectroscopy are interpreted based on prior knowledge, or at least “postulation” to the chemical structures of the analyte compounds . Recently, a dereplication strategy utilizing Global Natural Product Social (GNPS) molecular networking has been proposed to leverage the structural features of known compounds to decrypt the tandem mass spectra of unknown compounds . Specifically, cosine similarities among each pair of tandem mass spectra of individual specialized metabolites are calculated, of which the compounds with similar chemical structures are prone to cluster together .…”
Section: Introductionmentioning
confidence: 99%
“…13 Recently, a dereplication strategy utilizing Global Natural Product Social (GNPS) molecular networking has been proposed to leverage the structural features of known compounds to decrypt the tandem mass spectra of unknown compounds. [14][15][16][17] Specifically, cosine similarities among each pair of tandem mass spectra of individual specialized metabolites are calculated, of which the compounds with similar chemical structures are prone to cluster together. 17,18 This method provides an ability to rapidly categorize hundreds or thousands of specialized metabolomes collected from various organisms based on their chemical structures.…”
mentioning
confidence: 99%